2017
DOI: 10.1111/radm.12286
|View full text |Cite
|
Sign up to set email alerts
|

When do structural holes in employees' networks improve their radical creativity? A moderated mediation model

Abstract: Previous research has found a relationship between structural holes of knowledge networks, tie strength of knowledge networks, and creativity. Our study extends these findings by proposing that characteristics of R&D employees' team knowledge networks influence their acquired diversified knowledge from the team, which is critical to creativity. Our results based on 558 members of 92 R&D teams demonstrated that, in order to benefit from their broker position in acquiring diversified knowledge, R&D employees sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 48 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…Research has drawn on network structure conceptions such as 'small worlds', whereby dense clusters of network actors are linked to other clusters via a relatively small number of bridging links (Watts 1999;Gulati et al 2012). Similarly, research drawing on Burt's (1982Burt's ( , 1992Burt's ( , 2005 notion of structural holes, whereby actors who link previously unconnected actors within a network are considered to occupy privileged and central positions, has been applied to innovation studies (Stuart 1998;Ahuja 2000;Zaheer and Bell 2005;Massard and Mehier 2009;Zaheer and Soda 2009;Tortoriello 2015;Tang et al 2017;Kim et al 2018;Zang 2018). These studies all tend to identify network actor centrality as being associated with innovation outcomes, as well as the extent to which actors are embedded within either closed or open network structures.…”
Section: Network Structure and Spacementioning
confidence: 99%
“…Research has drawn on network structure conceptions such as 'small worlds', whereby dense clusters of network actors are linked to other clusters via a relatively small number of bridging links (Watts 1999;Gulati et al 2012). Similarly, research drawing on Burt's (1982Burt's ( , 1992Burt's ( , 2005 notion of structural holes, whereby actors who link previously unconnected actors within a network are considered to occupy privileged and central positions, has been applied to innovation studies (Stuart 1998;Ahuja 2000;Zaheer and Bell 2005;Massard and Mehier 2009;Zaheer and Soda 2009;Tortoriello 2015;Tang et al 2017;Kim et al 2018;Zang 2018). These studies all tend to identify network actor centrality as being associated with innovation outcomes, as well as the extent to which actors are embedded within either closed or open network structures.…”
Section: Network Structure and Spacementioning
confidence: 99%
“…Based on our results we offered some recommendations about use of different structural holes measures in the context of simple and complex networks whether related to innovation, partnerships, team management etc. (Tang et al ., 2017; Zang, 2018), business sector of the organization (Grandinetti, 2018) or governance model (Zhao and Burt, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The position of structural holes helps actor access different knowledge [43]. In other words, the crucial role of a "bridge" gives actors more opportunity to attain diversified external knowledge [30][31][32]45]. As Burt [46] pointed out, actors occupying structural holes face chances to exploit and transfer diverse knowledge.…”
Section: The Impact Of Organizations' Accessed External Scientific Knmentioning
confidence: 99%
“…Firstly, our results revealed that organizations' structural holes and degree centrality of scientific cooperation network positively influence their scientific knowledge generation. The rich structural holes help bring variety of external heterogeneous knowledge [30][31][32][34][35][36]45]. Organizations with central position can access more external knowledge, and thus have more opportunities of knowledge-recombination [51] and accessing varied knowledge [33].…”
Section: Main Findingsmentioning
confidence: 99%